Award of the Tribunal of Arbitration [electronic resource] : constituted under Article I of the treaty concluded at Washington on the 29th February, 1892, between Her Britannic Majesty and the United States of America. - Bering Sea Tribunal of Arbitration. (London : Printed for H.M.S.O. by Harrison and Sons, 1893)
Text in English and French. Original issued in series: [Command papers / Great Briatin. Parliament] Cd. 7107. At head of title: United States. No. 10 (1893). Behring Sea Arbitration. "Presented to both Houses of Parliament by Command of Her Majesty. August 1893." Electronic reproduction. Mode of access: Internet. 44